2015
DOI: 10.4172/2469-9837.1000143
|View full text |Cite
|
Sign up to set email alerts
|

Developing Social-emotional Vocabulary to support Self-regulation for Young Children at Risk for Emotional and Behavioral Problems

Abstract: The current study was designed to examine the effects of a social-emotional learning intervention using interactive storybook reading, SELF: Social-Emotional Learning Foundations, on the vocabulary growth of kindergarten and first grade students at risk for emotional and behavioral difficulties. Because SELF was intended to promote students' overall social-emotional development, the specific focus of this study was on Vocabulary related to social-emotional learning. A pretest-posttest control group design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Daunic et al (2013) reported a preliminary version of SELF improved executive function, internalizing behavior, and school-related competence assessed by teachers. In addition, in another pilot study, Santiago-Poventud and colleagues (2015) found positive effects of SELF on expressive and receptive vocabulary regardless of baseline language skills. Most recently, in a pretest–posttest cluster-randomized efficacy trial (Daunic, Corbett, Smith, Algina, et al, 2021), SELF evidenced a significant positive impact on multiple outcomes for 1,154 K–Grade 1 students at risk for EBD, including standardized measures of SEL-related competencies, self-regulation, and school adjustment, and a researcher designed measure of SEL-related vocabulary.…”
Section: The Social-emotional Learning Foundations Interventionmentioning
confidence: 90%
See 1 more Smart Citation
“…Daunic et al (2013) reported a preliminary version of SELF improved executive function, internalizing behavior, and school-related competence assessed by teachers. In addition, in another pilot study, Santiago-Poventud and colleagues (2015) found positive effects of SELF on expressive and receptive vocabulary regardless of baseline language skills. Most recently, in a pretest–posttest cluster-randomized efficacy trial (Daunic, Corbett, Smith, Algina, et al, 2021), SELF evidenced a significant positive impact on multiple outcomes for 1,154 K–Grade 1 students at risk for EBD, including standardized measures of SEL-related competencies, self-regulation, and school adjustment, and a researcher designed measure of SEL-related vocabulary.…”
Section: The Social-emotional Learning Foundations Interventionmentioning
confidence: 90%
“…The SELF Vocabulary Measure is a researcher-developed and individually administered measure to assess knowledge of SEL-related vocabulary (Santiago-Poventud et al, 2015). For each of 20 words assessed at each grade level, a member of the research team trained in administering the instrument asked student participants to (A) provide a definition, (B) use the word in an example, and (C) apply the word to answer a multiple-choice question with three options.…”
Section: Methodsmentioning
confidence: 99%
“…The teacher asked the children to pay attention to the teacher's story-telling and what the teacher said to the puppet. A related study also indicated that using seven effective strategies to improve children's vocabulary had a significant relationship with students' social emotional vocabulary scores (Daunic 2015).…”
Section: Emotional Lexicon For Childrenmentioning
confidence: 95%
“…Thus, Francois et al proposed the Xception architecture. Through depth-wise separable convolution technology, the speed of convolution operations is further improved and the amount of data is reduced (Daunic 2015). In the past, the general CNN convolution operation method convolved with each filter for each layer of data.…”
Section: Emotional Detectionmentioning
confidence: 99%
“…De ahí que, el procesamiento de las emociones puede verse significativamente influenciado tan pronto como los niños aprenden a usar palabras y etiquetas verbales para la expresión y la categorización de las emociones (Herbert et al, 2018). En esta línea, se ha demostrado que la lectura guarda una estrecha relación con el aumento de vocabulario emocional y el aumento de los niveles de empatía (Dylman et al, 2020); y que el entorno influye en la adquisición de este vocabulario, de modo que un contexto rico en alfabetización favorece la cognición, el lenguaje, la metacognición y la autorregulación (Santiago-Poventud et al, 2015).…”
Section: Introductionunclassified